2007
DOI: 10.1111/j.1365-246x.2007.03402.x
|View full text |Cite
|
Sign up to set email alerts
|

Crustal root beneath the highlands of southern Norway resolved by teleseismic receiver functions

Abstract: SUMMARY Teleseismic data have been collected with temporary seismograph stations on two profiles in southern Norway. Including the permanent arrays NORSAR and Hagfors the profiles are 400 and 500 km long and extend from the Atlantic coast across regions of high topography and the Oslo Rift. A total of 1071 teleseismic waveforms recorded by 24 temporary and 8 permanent stations are analysed. The depth‐migrated receiver functions show a well‐resolved Moho for both profiles with Moho depths that are generally acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 44 publications
(57 reference statements)
3
54
0
Order By: Relevance
“…3C) by Stratford et al (2009) and have been used as additional input data for 3D density modelling, also with partial use of data from Maystrenko & ScheckWenderoth (2013). The refraction seismic results of Stratford et al (2009) are also generally consistent with the previous receiver function results by Svenningsen et al (2007) and can therefore be considered as reliable high-quality data for Moho depth beneath SW Norway. The lithosphere-asthenosphere boundary has been derived from previously published data, such as the seis-8C).…”
Section: Data For the Deep Part Of The Study Areasupporting
confidence: 76%
See 1 more Smart Citation
“…3C) by Stratford et al (2009) and have been used as additional input data for 3D density modelling, also with partial use of data from Maystrenko & ScheckWenderoth (2013). The refraction seismic results of Stratford et al (2009) are also generally consistent with the previous receiver function results by Svenningsen et al (2007) and can therefore be considered as reliable high-quality data for Moho depth beneath SW Norway. The lithosphere-asthenosphere boundary has been derived from previously published data, such as the seis-8C).…”
Section: Data For the Deep Part Of The Study Areasupporting
confidence: 76%
“…In contrast, the regional crustal structure of the northern North Sea and the adjacent continent is less well known compared with the sedimentary level. Our knowledge of the structure of the crystalline crust within the study area is mainly based on 2D deep reflection and refraction seismic lines (Calcagnile, 1982;Christie, 1982;Barton & Wood, 1984;Klemperer & White, 1989;Iwasaki et al, 1994;McBride & England, 1999;Abramovitz & Thybo, 2000;Christiansson et al, 2000;Nielsen et al, 2000;Erickson, 2004;Sandrin & Thybo, 2008;Sandrin et al, 2009;Stratford et al, 2009;Stratford & Thybo, 2011;Thybo & Nielsen, 2012;Kvarven et al, 2014Kvarven et al, , 2016 and teleseismic receiver functions (Ottemöller & Midzi, 2003;Svenningsen et al, 2007). Furthermore, several potential field studies have revealed additional important features of the deep structure within the study area both in 2D (Åm, 1973;Hovland, 1987;Olesen et al, 2004;Lyngsie et al, 2006;Fichler et al, 2011;Ebbing et al, 2012;Kvarven et al, 2014;Nirrengarten et al, 2014 and others) and in 3D (Tesauro et al, 2007;Yegorova et al, 2007;Kaban et al, 2010;).…”
Section: Introductionmentioning
confidence: 99%
“…From previous studies on crustal thickness and gravity data (e.g. Balling 1980;Svenningsen et al 2007;Ebbing et al 2012), we find that the high topography of the Southern Scandes Mountains is isostatically compensated mainly by a thickened crust, thought to be largely of Caledonian age, resulting from continentcontinent collision between Baltica and Laurentia (cf. introduction and Nielsen et al 2009).…”
Section: Svecofennian Sveconorwegian and Caledonian Unitsmentioning
confidence: 53%
“…Crustal velocity and thickness are mainly determined by seismic refraction experiments and by analyses of receiver functions (EUGENO-S Working Group 1988; Iwasaki et al 1994;Svenningsen et al 2007;Olsson et al 2008;Sandrin & Thybo 2008;Stratford et al 2009;Stratford & Thybo 2011;. For a recent compilation and analysis, see Artemieva & Thybo (2013).…”
Section: Previous Studiesmentioning
confidence: 99%
“…It has been shown that in some cases, high-and lowvelocity relics generated by subducted slab or crustal and mantle lithospheric delamination resulting in the upwelling of the asthenospheric mantle can be retained for a long time, even a couple of billion years (Cook et al, 1999;Balling, 2000;Svenningsen et al, 2007;Zhai et al, 2007;He et al, 2015). These low-and high-velocity structures can be imaged by tomography (Zhao et al, 1992(Zhao et al, , 1994Zhao et al, 2016).…”
Section: Mechanism Of the Emeishan Lip Formationmentioning
confidence: 99%